1971
DOI: 10.1007/bf02282469
|View full text |Cite
|
Sign up to set email alerts
|

Dropouts from higher education: Toward an empirical model

Abstract: RESUMENLa deserción estudiantil universitaria es uno de los mayores problemas con el que se enfrenta el sistema de educación superior. Las autoridades de las universidades han venido presentando gran preocupación debido a que ante el aumento en la demanda de la educación superior, el número de alumnos que logra culminar sus estudios superiores no es el esperado, evidenciándose el abandono de un gran número de estudiantes en los primeros semestres. Esto genera problemas financieros en las universidades. La fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
378
0
41

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(466 citation statements)
references
References 7 publications
12
378
0
41
Order By: Relevance
“…Spady [5] and Tinto [6] argue that a student's persistence/withdrawal decision is the result of a long series of interactions between the student and the academic and social systems of the institution. Lam [7] points out the various reasons for dropout-student status, residence, financial sources, distance of hometown from the university, goal fulfilment, and satisfaction with the overall university atmosphere-which are useful in making predictions.…”
Section: Research Trends Related To Dropout At the University Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Spady [5] and Tinto [6] argue that a student's persistence/withdrawal decision is the result of a long series of interactions between the student and the academic and social systems of the institution. Lam [7] points out the various reasons for dropout-student status, residence, financial sources, distance of hometown from the university, goal fulfilment, and satisfaction with the overall university atmosphere-which are useful in making predictions.…”
Section: Research Trends Related To Dropout At the University Levelmentioning
confidence: 99%
“…He shows that college grades seem more a product of selection than of socialization. Moreover, according to Spady [5], psychological factors such as institutional commitment and perceived social integration (i.e., a subjective sense of belonging and fitting in) have a stronger influence on the decision to drop out in one's first year.…”
Section: Research Trends Related To Dropout At the University Levelmentioning
confidence: 99%
“…Tinto (1975) develops the student integration model to consider the reasons for student attrition. This model draws on earlier work by Spady (1970Spady ( , 1971, which in turn is influenced by Durkheim's theory of suicide (1952). The student integration model considers that the personal characteristics of students influence their initial commitment to the goals of studying and the institution, from then on (primarily in the first year of study) social and academic experiences lead to greater or lesser integration, which ultimately leads to the student's re-evaluation of their commitment to the goals and the institution.…”
Section: Research Into Retention In Higher Educationmentioning
confidence: 99%
“…These five variables were then linked indirectly to the dependent variable, dropout decision, through two intervening variables (satisfaction and institutional commitment). Subsequently, Spady (1971) designed and executed an empirical study, the findings of which resulted in his addition of structural relations to the model and "…a revision of the relationships among the components in the model " (Summers, 2003, p. 67). The results of the empirical study indicated, "Over a four-year period…formal academic performance is clearly the dominant factor in accounting for attrition among both sexes" (Spady, 1971, p. 38).…”
mentioning
confidence: 99%